The Usage and Impact of ICTs during the Covid-19 Pandemic - Yang, Shengnan; Zhu, Xiaohua; Fichman, Pnina (Routledge Studies in Library and Information Science, 2023)
This book takes a holistic view of the roles of ICTs during the pandemic through the lens of social informatics, as it is critical to our understanding of the relations between society and technology. Specific attention is given to various stakeholders and social contexts, with analysis at the individual, group, community, and society levels. Pushing the boundaries of information science research with timely and critical research questions, this edited volume showcases information science research in the context of COVID-19, by specifically accentuating sociotechnical practices, activities, and ICT interventions during the pandemic. Its social informatics focus appeals to a broad audience, and its global and international orientation provides a timely, innovative, and much-needed perspective to information science. This book is unique in its interdisciplinary nature as it consists of research studies on the intersections between ICTs and health, culture, social interaction, civic engagement, information dissemination, work, and education. Chapters apply a range of research methods, including questionnaire surveys, content analyses, and case studies from countries in Asia, Europe, and America, as well as global and international comparisons. The book's primary target audience includes scholars and students in information and library science, particularly those interested in the social aspect of the information society. It may be of interest to information professionals, library practitioners, educators, and information policymakers, as well as scholars and students in science and technology studies, cultural studies, political science, public administration, sociology, and communication studies.